Identity, Power and Otherness: A Postcolonial-Oriental Reading of Daniel Defoe’s Robinson Crusoe - Nforbin, Gerald Niba (Advances in Social Sciences Research Journal, 2023)
This paper offers a postcolonial-oriental reading of Daniel Defoe’s Robinson Crusoe. The study employs the postcolonial theory, principally, Edward Said’s orientalism and his concept of contrapuntal reading, which investigates the contextual circumstances of a text’s production. Such a reading demonstrates that, in plot, setting, thematic content and characterization, Robinson Crusoe is a prototypical colonial narrative, shaped by colonial discourse and reflects the dominant imperialist ideologies of its time concerning race, identity and otherness. British colonialism informs nearly every feature of Robinson Crusoe, and, in its orientalist rhetoric, the novel clearly reproduces the imperialistic ideology of its time. Friday’s existence in the text generates oriental ‘othering’ (which establishes his identity as the colonized) and serves both as a reminder of the colonial expansion of the British Empire and of the era’s dominant, imperialistic discourse and perceived superiority of Englishness. Imperialism started to influence English national identity as colonizer as early as the eighteenth centuries with the English thinking more highly of themselves on account of their contact with colonized peoples, as epitomized in the character and personality of Defoe’s protagonist, Robinson Crusoe. As narrator, Crusoe’s attitude towards non-Europeans and his use of racial slurs are clearly in line with the era’s orientalist rhetoric, which traditionally attributed traits outside British ideal values and accepted norms to the colonized or Eastern other.